Cho \(F(x)\) là một nguyên hàm của hàm số \(f(x)=\dfrac{1}{2x+1}\), biết \(F(0)=2\). Tính \(F(1)\).
\(F(1)=\dfrac{1}{2}\ln3+2\) | |
\(F(1)=\ln3+2\) | |
\(F(1)=2\ln3-2\) | |
\(F(1)=\dfrac{1}{2}\ln3-2\) |
Chọn phương án A.
\(\begin{eqnarray*}
&\displaystyle\int\limits_{0}^{1}f(x)\mathrm{\,d}x&=F(x)\bigg|_0^1\\
\Leftrightarrow&\displaystyle\int\limits_{0}^{1}\dfrac{1}{2x+1}\mathrm{\,d}x&=F(1)-F(0)\\
\Leftrightarrow&\dfrac{1}{2}\ln|2x+1|\bigg|_0^1&=F(1)-2\\
\Leftrightarrow&\dfrac{1}{2}\ln3+2&=F(1).
\end{eqnarray*}\)
Chọn phương án A.
\(F(x)=\displaystyle\int\dfrac{1}{2x+1}\mathrm{\,d}x=\dfrac{1}{2}\ln|2x+1|+C\).
Vì \(F(0)=2\) nên $$\dfrac{1}{2}\ln|2\cdot0+1|+C=2\Leftrightarrow C=2$$Vậy \(F(x)=\dfrac{1}{2}\ln|2x+1|+2\).
Suy ra \(F(1)=\dfrac{1}{2}\ln|2\cdot1+1|+2=\dfrac{1}{2}\ln3+2\).